Analisis Pengetahuan Masyarakat Kota Pekanbaru tentang Wisata Syariah - Zulkifli, Zulkifli; Bakhri, Boy Syamsul; Yusuf, Muhammad (UIR Press, 2018)
The background of this research emerged from the phenomenon that there is a global economic development at this time, namely the seven sectors of Islamic economy that have increased significantly. One of them is sharia tourism, whereas the sector carries the concept of halal in each of its products. In Pekanbaru City, sharia tourism experiences a very significant development with the vision of Pekanbaru City as Madani city. For this reason, the writers want to examine how the understanding of Pekanbaru City people about sharia tourism. The purpose of this study was to find out how well the enderstanding of Pekanbaru City people about sharia tourism. The method used in this study is a qualitative descriptive method with qualitative research. The population in this study was 1,038,118 people. The sample is taken from the entire population of 100 people, with the sampling technique using the Slovin formula. Based on the results of research on the analysis of people’s undersanding in Pekanbaru City about sharia tourism which was processed through respondents' answers, it can be concluded that P = 83.86%, which means that the analysis of the people’s understanding in Pekanbaru City on sharia tourism showed